Physical Origin of Dual-Emission of Au–Ag Bimetallic Nanoclusters - Peng, Bo; Zheng, Liu-Xi; Wang, Pan-Yue; Zhou, Jia-Feng; Ding, Meng; Sun, Hao-Di; Shan, Bing-Qian; Zhang, Kun (Frontiers in Chemistry, 2021)
On the origin of photoluminescence of noble metal NCs, there are always hot debates: metal centered quantum size confinement effect Vs ligand centered surface state mechanism. Herein, we provided solid evidences that, structural water molecules (SWs) confined in the nanocavity formed by surface-protective-ligand packing on the metal NCs are the real luminescent emitters of Au-Ag bimetal NCs. The Ag cation mediated Au-Ag bimetal NCs exhibit the unique pH-dependent dual-emission characteristic with larger Stokes shift up to 200 nm, which could be used as potential ratiometric nanosensors for pH detection. Our results provide a completely new insight on the understanding of the origin of PL of metal NCs, which elucidates the abnormal PL emission phenomena, including solvent effect, pH-dependent behavior, surface ligand effect, multiple emitter centers, large-Stoke’s shift, etc.